El saber para vivir de los asháninka - Vilchez Jiménez, Elsa (2007)
The Ashaninka, Amazonian people of Peru, demonstrate the need to go beyond interdisciplinarity for knowledge and recognition of the dialogue of knowledge, for which diverse rationalities and traditions must be confronted. It is recognized that environmental knowledge opens the dialogue of knowledge by interweaving a complex web of knowledge, thoughts, cosmovisions and discursive formations that overflows the field of scientific logos.As a sample of the Ashaninka's knowledge for living, we will present schematically the lexical fields of the Ashaninka cosmovision.